"The Galigir Room": a resourced provision for young people with social, emotional and mental health difficulties (SEMH) in their first years at secondary school. Issue 2 (24th May 2020) - Greer, Julie
Abstract : This paper examines the values, vision and practice originally outlined in a proposal for a secondary phase resourced provision for young people with social, emotional and mental health (SEMH) challenges. The provision was based on a well‐established model (the 'Jarjums Room') which had been implemented in Cherbourg Primary School in Eastleigh, England. The article offers a first‐hand narrative account of the way that this initiative, the 'Galigir Room', was conceptualised, successfully embraced and implemented, thanks to the commitment of a senior leadership team, a group of staff and governors and the foresight and support of the local secondary school.